Effect of dietary l-carnitine and ractopamine-hcl (paylean) on the metabolic response to handling in growing-finishing pigs - B W James; J C Woodworth; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
Two experiments (384 pigs) were conducted to determine the interactive effect of dietary L-carnitine and ractopamine·HCl (Paylean) on the metabolic response to handling. Experiments were arranged as split plots, with handling as the main plot and diet as subplots (4 pens/treatment). Dietary Lcarnitine (0 or 50 ppm) was fed from 85 lb to the end of the trials (260 lb) and Paylean (0 or 20 ppm) was fed for the last 4 wk of each trial. At the end of each trial, two pigs per pen were assigned to one of two handling treatments. Gentle-handled pigs were moved at a moderate pace three times through a 164-ft course and up and down a 15° loading ramp. Nongentle-handled pigs were moved at a faster pace, up and down a 30° ramp, and were shocked by an electrical prod. Blood was collected immediately before and after handling in Exp. 1 and immediately after and 1 h after handling in Exp. 2. Feeding Paylean increased (P0.10) effect of L-carnitine on growth performance in either trial. In Exp. 1 and 2, nongentle handling increased (P0.96) by 1 h post-handling. Lactate, LDH, cortisol, and temperature changes from immediately posthandling to 1 h post-handling were not different for pigs fed L-carnitine or Paylean, suggesting that L-carnitine did not decrease recovery time of pigs subjected to non-gentle handling. These results demonstrate the importance of proper handling technique to minimize stressful events during the loading and transporting of pigs, regardless of whether either of these feed additives is being fed. This was evident by the large magnitude of the metabolic changes observed for the handling treatments, whereas in general the magnitude of metabolic changes from the dietary treatments was much smaller. Nonetheless, pigs fed Paylean are more susceptible to stress when handled aggressively, compared with pigs not fed Paylean. Dietary L-carnitine did not alleviate the effects of stress when fed in combination with Paylean.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Swine; L-carnitine; Pigs; Ractopamine HCL